Prevention and protection technologies – How do the growers get ready for climate change? - D. D. Nagyné; Z. Szabó; J. Nyéki; M. Soltész (International Journal of Horticultural Science, 2011)
Within the sector of fruit growing, climate change related tasks cover a rather wide range of activities. According to what is claimed by the literature, all decisions impacting the sector should be made conformably with climate change in order to advance an increase in yield security. This, regardless of the impacts of climate change, is also one of the key questions in fruit growing. Regarding protection against extreme weather events, in addition to technological and technical elements, the level of importance assumed by farmers for the abovementioned protection techniques as well as the type and extent they intend to use of this in practice are also worth of studying. This ongoing research beginning in 2009 mainly focuses on studying the opinions of fruit farmers making up the target group for this analysis. The questionnaire survey primarily intends to study their knowledge on the definition of climate change as reactivity to unfavourable weather events occurring in the growing. The study aims at providing a realistic view on the fruit-farmers’ knowledge on climate change and on how technological elements, new technical solutions applicable to mitigate damage are used during production.